2020
DOI: 10.1002/anie.202005643
|View full text |Cite
|
Sign up to set email alerts
|

Room‐Temperature Formation Pathway for CdTeSe Alloy Magic‐Size Clusters

Abstract: Little is known about the pathway of room‐temperature formation of ternary CdTeSe magic‐size clusters (MSCs) obtained by mixing binary CdTe and CdSe induction period samples containing binary precursor compounds (PCs) of MSCs, monomers (Ms), and fragments (Fs). Also, unestablished are dispersion effects that occur when as‐mixed samples (without incubation) are placed in toluene (Tol) and octylamine (OTA) mixtures. The resulting ternary MSCs, exhibiting a sharp optical absorption peak at 399 nm, are labelled Cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 25 publications
(81 citation statements)
references
References 64 publications
1
79
1
Order By: Relevance
“…The formation of CdTeSe PC-399 MSCs is described in Part ao fScheme S3, with the reaction from CdTe PC-371 following Equation ( 1). [1] Here, Step 1represents the transformation from CdTeSe PC-399 and CdTeSe PC-422, and is covered by Equation ( 2) and is rate-determining. Steps 2/3 and 4/5 signify the reversible transformations between the two corresponding pairs of MSCs and their PCs.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of CdTeSe PC-399 MSCs is described in Part ao fScheme S3, with the reaction from CdTe PC-371 following Equation ( 1). [1] Here, Step 1represents the transformation from CdTeSe PC-399 and CdTeSe PC-422, and is covered by Equation ( 2) and is rate-determining. Steps 2/3 and 4/5 signify the reversible transformations between the two corresponding pairs of MSCs and their PCs.…”
Section: Resultsmentioning
confidence: 99%
“…2). The different rates between the PC formation and PC transformation to MSCs can be found elsewhere 25,52 .…”
Section: Discussionmentioning
confidence: 99%
“…ForaMSC-A to MSC-B transformation, the three steps are MSC-A to PC-A, PC-A to PC-B,and PC-B to MSC-B.However,the reported transformations are limited to those between two binary MSCs, [3][4][5][6][7][8][9][10] or between ab inary MSC and at ernary MSC. [1,2,5] Before the present study, transformations in ternary MSCs have not been reported.…”
Section: Introductionmentioning
confidence: 84%
“…It is established that colloidal semiconductor compound magic-size clusters (MSCs) have particular precursor compounds (PCs). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Thef ormer (MSC-A) exhibits distinct optical absorption peaking at ac onstant wavelength A expressed in nanometers (nm), while the latter (PC-A) is usually transparent at this wavelength Aa nd to longer wavelengths.T he MSCs and their counterpart PCs are quasi isomers and transform mutually via reversible intramolecular reorganization. Furthermore,t he transformation between types of MSCs has been observed, [1][2][3][4][5][6][7][8][9][10] following ap athway that appears to be PC-enabled comprising three key steps (Scheme S1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation